1978
DOI: 10.1055/s-0028-1093431
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Changes in Serum Metabolites and Hormones in Lean and Obese Zucker Rats

Abstract: A study of diurnal patterns of serum hormone levels was made in genetically lean and obese Zucker rats. Serum glucose and insulin were elevated in the obese through the 24-hour period; immunoreactive insulin being 12 times higher in the obese rat. A similar pattern of serum hormone levels in lean and obese rats was found for triiodothyronine, thyroid stimulating hormone and prolactin. At peak levels, prolactin was 2.5 times higher in lean than obese rats (P is less than .01). Thyroxine levels tended to be lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0
1

Year Published

1981
1981
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(50 citation statements)
references
References 9 publications
4
45
0
1
Order By: Relevance
“…The answer to this problem most likely lies not in the stress of the sacrifice procedure, but rather in the age of the animals used. The form of the corticosterone rhythm has been shown to vary greatly with age [Martin et al, 1978]. The lack of any significant difference in liver glycogen, pineal serotonin, and cere bellar magnesium and cerebellar calcium be tween those animals sacrificed by pentobar bital and those killed by CCF inhalation also argues against any significant influence of the sacrifice procedure in the observed results.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…The answer to this problem most likely lies not in the stress of the sacrifice procedure, but rather in the age of the animals used. The form of the corticosterone rhythm has been shown to vary greatly with age [Martin et al, 1978]. The lack of any significant difference in liver glycogen, pineal serotonin, and cere bellar magnesium and cerebellar calcium be tween those animals sacrificed by pentobar bital and those killed by CCF inhalation also argues against any significant influence of the sacrifice procedure in the observed results.…”
Section: Discussionmentioning
confidence: 47%
“…Pentobarbital was deemed preferable to decapitation for the following reasons: (1) the technique provided a greater volume of blood with less contamination by other tis sues: (2) 1.540 0 .1 0 < 3.558 p < 0.01 (11,97) p < 0.20 (11,97) cycle, and (3) we regarded this procedure as more humane. The plasma corticosterone values (an indicator of stress) found in the control animals were well within values re ported by other investigators using other methods of sacrifice, including decapitation [Kreiger, 1972;Martin et al, 1978;Bahnent et al. 1977], It was puzzling that the expected significant cosinor results for control animals in plasma corticosterone was not observed.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Clonidine-induced food intake is en hanced during periods of increased plasma corticosterone lev els [31]. Since obese Zueker rats have elevated daytime plasma corticosterone levels [35], the greater response to clonidinestimulated food intake in obese animals could also be medi ated by a higher sensitivity of « 2-adrenoceptors, especially since corticosterone has been shown to upregulate « 2-recep tors within the PVN [36]. Corticosterone may also control feeding behavior by other mechanisms, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This last aspect has to be more thoroughly investigated. It has been observed that mammal obesities are frequently accompanied by abnormally depressed plasma GH concentrations (Sinha et al, 1975 ;Martin et al, 1978 ;Finkelstein et al, 1986 …”
Section: Introductionmentioning
confidence: 99%